Debates in allergy medicine: Molecular allergy diagnosis with ISAC will replace screenings by skin prick test in the future - E. Jensen-Jarolim; A.N. Jensen; G.W. Canonica (World Allergy Organization Journal, 2017)
In today’s clinical practice patients’ skin is used as screening organ for diagnosing type 1 allergy. According to European guidelines skin prick testing with a panel of 18 allergen extracts is recommended, in the US between 10 to 50 allergens are used. The specificity and sensitivity of skin testing is individually highly variable depending on age, body mass, and skin barrier status. In atopic inflammation skin testing gives more false positive results. Smaller skin area and strain limits prick testing in small children. Although the risk for systemic reactions in skin prick testing is very small, emergency medications must be available. Considering the fact that IgE is the only reliable biomarker for type I allergy, upfront IgE screening with ISAC, followed by fewer skin tests to approve positive sensitizations, is proposed. It is time to arrive in the age of molecular allergy diagnosis in daily patient care.